MTCH2 regulates NRF2-mediated RRM1 expression to promote melanoma proliferation and dacarbazine insensitivity - Xuedan Zhang; Enjiang Li; Yingmin Kuang; Yanlong Gai; Yu Feng; Yu Huang; Zhenyan Wei; Junzi Niu; Song Yu; Zhe Yang; Qiao Zhang; Buqing Sai; et al. (Cell Death and Disease)
Abstract Melanoma is among the 10 most prevalent malignant tumors, posing a significant threat to human health. A detailed understanding of the molecular mechanisms driving its progression is crucial for advancing treatment strategies and outcomes. Based on bioinformatic analysis and experimental validation, this study identified mitochondrial carrier homolog 2 (MTCH2) as a key regulator of melanoma proliferation. Mechanistically, MTCH2 enhanced the expression and nuclear translocation of nuclear factor (erythroid-derived-2)-like 2 (NRF2), which up-regulated ribonucleotide reductase subunit M1 (RRM1) expression, thereby promoting melanoma cell proliferation. Targeting RRM1 in combination with dacarbazine significantly inhibited tumor growth in nude mouse xenograft models. These findings elucidate a mechanistic link between MTCH2 and the NRF2-RRM1 axis in melanoma proliferation and highlight potential therapeutic targets for intervention.